Targeting low-druggability bromodomains: fragment based screening and inhibitor design against the BAZ2B bromodomain. - Ferguson, F; Fedorov, O; Chaikuad, A; Philpott, M; Muniz, JR; Felletar, I; von Delft, F; Heightman, T; Knapp, S; Abell, C; Ciulli, A (2013)
Bromodomains are epigenetic reader domains that have recently become popular targets. In contrast to BET bromodomains, which have proven druggable, bromodomains from other regions of the phylogenetic tree have shallower pockets. We describe successful targeting of the challenging BAZ2B bromodomain using biophysical fragment screening and structure-based optimization of high ligand-efficiency fragments into a novel series of low-micromolar inhibitors. Our results provide attractive leads for development of BAZ2B chemical probes and indicate the whole family may be tractable.